2018
DOI: 10.1002/eco.2021
|View full text |Cite
|
Sign up to set email alerts
|

Variability in leaf wettability and surface water retention of main species in semiarid Loess Plateau of China

Abstract: Leaf wettability, adhesion or repulsion of water drops, varies greatly among species and plays an important role in plant-soil hydrological relations. This study aimed to examine the variability in leaf wettability among species in different habitats and growth periods, and their relationships with plant surface water retention in the semiarid Loess Plateau of China. The leaf adaxial and abaxial contact angles, the surface water retention of leaves and individual plants, and general plant traits of 68 species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…The epicuticular wax layer constitutes the interface between leaf and atmosphere, and its main components have hydrophobic properties (Müller & Riederer, 2005). Our previous data also proved that leaves of gramineous and leguminous species were more water repellent (higher leaf contact angles) than those of compositae and rosaceous species (Xiong et al, 2018). Our previous data also proved that leaves of gramineous and leguminous species were more water repellent (higher leaf contact angles) than those of compositae and rosaceous species (Xiong et al, 2018).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The epicuticular wax layer constitutes the interface between leaf and atmosphere, and its main components have hydrophobic properties (Müller & Riederer, 2005). Our previous data also proved that leaves of gramineous and leguminous species were more water repellent (higher leaf contact angles) than those of compositae and rosaceous species (Xiong et al, 2018). Our previous data also proved that leaves of gramineous and leguminous species were more water repellent (higher leaf contact angles) than those of compositae and rosaceous species (Xiong et al, 2018).…”
Section: Discussionmentioning
confidence: 70%
“…When leaf contact angle is high, rainwater falling on leaf surface tend to drop more easily under the influences of gravity or any meteorological and biotic disturbances (Holder, 2013;Xiong et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonal changes of epicuticular wax load and composition are widespread and have been attributed to leaf ontogeny ( Jetter and Schäffer, 2001 ), temperature and water availability ( Ziv et al , 1982 ; Jordan et al , 1983 ), and erosion of wax crystals over time ( Neinhuis and Barthlott, 1998 ; Kang et al , 2018 ). Multiple studies report an increase in leaf wettability for broad-leaved trees towards the later part of the growth season, namely with increasing leaf age ( Neinhuis and Barthlott, 1998 ; Tranquada and Erb, 2014 ; Kang et al , 2018 ; Xiong et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, high LWR in new leaves, as compared to old leaves (Xiong et al, 2018), may be due to the erosive effect of environmental factors, such as precipitation and atmospheric deposition, on the waxes of the leaf surface (Baker and Hunt, 1986). Our results are consistent with a study measuring leaf wettability that showed that LWR values are higher during dry periods when compared to rainy ones, due to the amount of particles deposited on the leaf surfaces during the dry season (Xiong et al, 2018). We have observed that new leaves have higher carbon concentration, probably due to the higher concentrations of organic compounds in waxes, partially explaining the increase of beta diversity in February 2016, as compared to July 2015.…”
Section: Discussionmentioning
confidence: 99%